Preparasi Poli Tanin Untuk Meningkatkan Efisiensi Dye-Sensitized Solar Cell (DSSC) - Annisa Ade Putri; Hardeli Hardeli; Fajriah Azra; Minda Azhar (Jurnal Periodic Jurusan Kimia UNP, 2022)
DSSC (Dye-Sensitized Solar Cell) is a type of third-generation solar cell based on dye as a photon absorber that has been widely used. In this study, modifications were made to tannin dyes to increase double bonds. Modifications were also carried out on the semiconductor by means of TiO2-CuO doping. TiO2-CuO doping can reduce the energy gap thereby increasing the TiO2 conductivity. The dyes were characterized using FTIR and GC-MS, while the TiO2-CuO doping was characterized using a UV-DRS Spectrophotometer. The results of FTIR characterization of poly tannin dyes have shown specific groups of polymerization of polytannin glutaraldehyde resin. The characterization of TiO2-CuO doping showed a decrease in the energy gap of 3,2 eV to 3,01 eV. The highest efficiency was produced at 90 minutes polymer time with a tannin monomer concentration of 0,4 M of 8,332%.